2022
DOI: 10.3390/polym14122450
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Microplastics and Their Affiliated PAHs in Surface Water in Ho Chi Minh City, Vietnam

Abstract: Microplastic pollution has become a worldwide concern. However, studies on the distribution of microplastics (MPs) from inland water to the ocean and their affiliated polycyclic aromatic hydrocarbons (PAHs) are still limited in Vietnam. In this study, we investigated the distribution of MPs and PAHs associated with MPs in canals, Saigon River, and Can Gio Sea. MPs were found at all sites, with the highest average abundance of MPs being 104.17 ± 162.44 pieces/m3 in canals, followed by 2.08 ± 2.22 pieces/m3 in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 89 publications
(134 reference statements)
0
2
0
Order By: Relevance
“…discharge into the river estimated at 200,000 m 3 d -1 ; [37]) at that time were an important source of fiber contamination in the Saigon River and its canal system. The tendency of higher concentrations observed in the denser urban zone with low wastewater treatment capacity was confirmed in the same system [31][32]. It was also evidenced in the Red River system with a tendency of decreasing concentrations of microplastics in the Day River surface water from places with high population density to low population density [38] and in the Bach Dang Estuary with decreasing concentrations towards the estuary mouth probably due to water mixing with seawater [35].…”
Section: ) Fate and Transfer Of Microplastics In The Vietnamese Canal...mentioning
confidence: 76%
“…discharge into the river estimated at 200,000 m 3 d -1 ; [37]) at that time were an important source of fiber contamination in the Saigon River and its canal system. The tendency of higher concentrations observed in the denser urban zone with low wastewater treatment capacity was confirmed in the same system [31][32]. It was also evidenced in the Red River system with a tendency of decreasing concentrations of microplastics in the Day River surface water from places with high population density to low population density [38] and in the Bach Dang Estuary with decreasing concentrations towards the estuary mouth probably due to water mixing with seawater [35].…”
Section: ) Fate and Transfer Of Microplastics In The Vietnamese Canal...mentioning
confidence: 76%
“…To contextualize the PAH content of the spilled plastic, we compared our results to the PAH content measured and reported in the literature from 19 studies of plastic pellets (317 data points) and 15 studies of plastic debris (198 data points) found globally in the marine environment (Figure ). ,, When they arrived onshore on May 25, 2021, the white nurdles had an EPA16 PAH content (∼1260 ng/g) double the median for nurdles found globally in the marine environment (∼589 ng/g). It should be noted that many of these other studies examined nurdles with a yellowness index of 30 to 50, assuming that the yellowing indicated that these nurdles had been in the environment long enough to accumulate significant amounts of PAHs .…”
Section: Resultsmentioning
confidence: 99%
“…Comparison of PAH content for the plastic spilled during the M/V X-Press Pearl disaster analyzed in this study and plastic found in the ocean globally. Ranges of pollution level are those defined according to Yeo et al Data presented for the nurdles and plastic debris were collated from literature-reported absolute, mean, or median values, ,, details of which are available in Table S13. A comparison of each study is included in Figure S8.…”
Section: Resultsmentioning
confidence: 99%
“…Microplastic pollution is also prevalent in the region's freshwater ecosystems, which are essential for providing clean water for drinking and irrigation [6,7]. Several studies have found significant levels of MPs in freshwater sources across Southeast Asia, such as the Citarum River in Indonesia and the Saigon River in Vietnam [8,9].…”
mentioning
confidence: 99%
“…Thailand has implemented a plastic bag ban, and Indonesia has pledged to reduce marine plastic debris by 70% by 2025. The Association of Southeast Asian Nations (ASEAN) has launched a framework for action on marine debris, highlighting the importance of reducing plastic waste and promoting sustainable waste management practices in the region [7][8][9].…”
mentioning
confidence: 99%